State of Ambiguity Civic Life and Culture in Cuba's First Republic - Palmer, Steven; Piqueras, José Antonio; Cobos, Amparo Sánchez (Duke University Press, 2014)
Cuba's first republican era (1902-1959) is principally understood in terms of its failures and discontinuities, its first three decades and the overthrow of Machado seen at best as a prologue to the "real" revolution of 1959. This book brings together scholars from North America, Cuba, and Spain to challenge this narrative, presenting republican Cuba instead as a time of meaningful engagement-socially, politically, and symbolically. Addressing a wide range of topics-civic clubs and folkloric societies, science, public health and agrarian policies, popular culture, national memory, and the intersection of race and labor-the contributors explore how a broad spectrum of Cubans embraced a political and civic culture of national self-realization. These essays recast the first republic as a time of deep continuity in processes of liberal state- and nation-building that were periodically disrupted-but also reinvigorated-by foreign intervention and profound uncertainty.